Effects of maternal ageing on ICSI outcomes and embryo development in relation to oocytes morphological characteristics of birefringent structures. Issue 4 (29th May 2014) - Korkmaz, Cem; Tekin, Yesim Bayoglu; Sakinci, Mehmet; Ercan, Cihangir Mutlu
Summary: The aim of this study was to determine the morphological characteristics of the older reproductive aged women's oocytes and to reveal the influence of these characteristics on intra-cytoplasmic sperm injection (ICSI) outcomes. The oocytes of women older than 35 years of age were evaluated retrospectively. Non-invasive polarization microscopy (PolScope) examinations of mature oocytes were performed by measurement of meiotic spindles' length, area and retardance and zona pellucida thickness and retardance. Fertilization and conception competence and the correlation with the birefringent structures were assessed. Two hundred and thirteen mature oocytes from 54 women were evaluated with a PolScope. Length of the meiotic spindle was shown to be related to fertilization success of women with advanced maternal age. In conclusion, the PolScope is a useful device used to identify the oocyte quality. Quantitative measurements of meiotic spindle parameters may be valuable for the selection of high-quality oocytes that have the potential for embryo development in the in vitro fertilization (IVF) laboratory of women older than 35 years of age who are mostly poor responders.